2017
DOI: 10.1097/md.0000000000006699
|View full text |Cite
|
Sign up to set email alerts
|

Staged management of open Lisfranc injury

Abstract: There are still controversies on the management and outcome of open Lisfranc injury in available studies. This study evaluates the staged management of Lisfranc injury and its complications.Patients who received a staged strategy for open Lisfranc injury were reviewed.One patient with degloving injury suffered from partial skin and hallux necrosis which was treated by debridement, hallux amputation, definitive internal fixation, and local flap transfer on the 12th day after first stage management. A definitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In total, 462 Lisfranc patients, from 17 studies, were included in the analysis of complication rate, rate of revision surgery, and rate of secondary arthrodesis 8,11,12,15,18,20-24,26-31,33 (Table 1). A total of 363 (78.6%) of these patients were treated with ORIF, and 99 (21.4%) were treated with primary fusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 462 Lisfranc patients, from 17 studies, were included in the analysis of complication rate, rate of revision surgery, and rate of secondary arthrodesis 8,11,12,15,18,20-24,26-31,33 (Table 1). A total of 363 (78.6%) of these patients were treated with ORIF, and 99 (21.4%) were treated with primary fusion.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 521 Lisfranc patients, from 19 studies, reported AOFAS scores 8,12,[15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32] (Table 1). A total of 449 (86.2%) of these patients were treated with ORIF, and 72 (14.8%) were treated with primary fusion.…”
Section: Resultsmentioning
confidence: 99%